The use of guided composition through topics in order to help students develop their writing skills - Navarro Ramírez, Dunia (Universidad de Costa Rica, 2011)
The purpose of the following article is to share the results of a research project based on the application of a technique called Guided Composition through Topics, a thesis project in order to obtain the Licenciatura degree. The main objective of this research carried out with a group of tenth grade students, was to prove the effectiveness of this technique as an alternative source used by secondary school teachers to teach their pupils to write accurately. The technique was applied to a group of twenty-eight students from Colegio Patriarca San José in San Ramón, Alajuela whose ages ranged from fifteen to seventeen. The method was developed during eight sessions, four sessions for writing and four for the revising process, in which a self-correction code was used by the students. The purpose of this correction code was to prove its effectiveness by giving the students the opportunity of correcting themselves and improving their writing skills. After the eighth session, it was observed that the students showed improvement in their written abilities and developed self-confidence in writing.